2011
DOI: 10.1200/jco.2010.31.6208
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of Navitoclax (ABT-263), a Novel Bcl-2 Family Inhibitor, in Patients With Small-Cell Lung Cancer and Other Solid Tumors

Abstract: A B S T R A C T PurposeResistance to chemotherapy-induced apoptosis represents a major obstacle to cancer control. Overexpression of Bcl-2 is seen in multiple tumor types and targeting Bcl-2 may provide therapeutic benefit. A phase I study of navitoclax, a novel inhibitor of Bcl-2 family proteins, was conducted to evaluate safety, pharmacokinetics, and preliminary efficacy in patients with solid tumors. Patients and MethodsPatients enrolled to intermittent dosing cohorts received navitoclax on day Ϫ3, followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
375
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 511 publications
(384 citation statements)
references
References 34 publications
9
375
0
Order By: Relevance
“…The present investigation provides the biological rationale for these future clinical trials to evaluate ABT-737 alone or in combination with Mcl-1-reducing agents in MCL patients. Indeed, ABT-263 (navitoclax; Abbott), which is an orally bioavailable BH3-mimetic compound of the same class as ABT-737 and currently under investigation in hematologic and solid malignancies, could also be used as ABT-737 (13,(43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…The present investigation provides the biological rationale for these future clinical trials to evaluate ABT-737 alone or in combination with Mcl-1-reducing agents in MCL patients. Indeed, ABT-263 (navitoclax; Abbott), which is an orally bioavailable BH3-mimetic compound of the same class as ABT-737 and currently under investigation in hematologic and solid malignancies, could also be used as ABT-737 (13,(43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…We selected navitoclax, a dual Bcl-2/Bcl-x L inhibitor that is the subject of clinical trials (28)(29)(30)(31), and a novel MEK inhibitor, G-963 (Fig. 1B), to test the combination efficacy associated with targeting these proteins.…”
Section: Navitoclax Enhances the Activity Of A Mek Inhibitor In Cancementioning
confidence: 99%
“…This class of molecules is more effective in tumors with high levels of bcl-2/bcl-xL. ABT-263 is currently under investigation in various malignancies, either as a single drug compound, or in combination with other antitumor reagents (8,9) and has already reached clinical trials (10). Specifically, preclinical studies, involving ABT-263, have shown that it has activity against small cell lung cancer (SCLC) as well as acute lymphoblastic leukemia (7).…”
Section: Introductionmentioning
confidence: 99%